Plasma neurofilament light chain levels are predictors of disease activity in multiple sclerosis as measured by four-domain NEDA status, including brain volume loss - Szilasiová, Jarmila; Mikula, Pavol; Rosenberger, Jaroslav; Fedičová, Miriam; Gdovinová, Zuzana; Urban, Peter; Frigová, Lýdia (Multiple sclerosis, 2021)
BACKGROUND: The research is focused on sensitive biomarkers in multiple sclerosis (MS). OBJECTIVE: The aim of the study was to assess the relationship between plasma neurofilament light chain (pNfL) and disease activity as defined by the concept NEDA (no evident disease activity), including brain volumetry, in a cohort of MS patients treated with disease-modifying treatment (DMT). METHODS: Levels of pNfL (Single Molecule Array (SIMOA) technology) were examined in 95 RRMS (relapsing-remitting multiple sclerosis) patients and analyzed in relationship to NEDA-3 status and NEDA-BVL (brain volume loss; NEDA-3 extended by brain volumetry) during the last 12 months. The statistical model was developed using logistic regression analysis, including the independent variables: demographic, clinical, and magnetic resonance imaging (MRI) data. Dependent variables were NEDA-3 and NEDA-BVL status. RESULTS: The mean age of the study participants (n = 95, 62% females) was 37.85 years (standard deviation (SD) = 9.62) and the median disability score was 3.5 (2.5-4.1). Receiver operating characteristics (ROC) analysis showed that pNfL predicts NEDA-3 (the sensitivity and specificity of the model were 92% and 78%, respectively, p < 0.001) and NEDA-BVL status (the sensitivity and specificity were 80% and 65%, respectively, p < 0.001). CONCLUSION: The results show that pNfL levels are a useful biomarker of disease activity determined by NEDA-BVL status, including brain MRI-volumetry in patients with RRMS.
Keywords: dospělí; relabující-remitující roztroušená skleróza; Intermediate Filaments; Magnetic Resonance Imaging; intermediární filamenta; mozek; lidé; Female; Multiple Sclerosis; mužské pohlaví; Male; magnetická rezonanční tomografie; Brain; Multiple Sclerosis, Relapsing-Remitting; roztroušená skleróza; Adult; ženské pohlaví; Humans